Electrochemical behaviour of copper in potassium thiocyanate : I. Dissolution, passivation and pitting processes - Figueroa, M. G. (1986)
The electrochemical behaviour of copper in borate buffers containing KSCN is studied by potentiostatic and potentiodynamic techniques complemented with scanning electron microscopy and EDAX. The voltammetric response can be divided into three regions. Region I is related to the formation of a Cu(SCN)ad monolayer followed by a porous tridimensional growth of CuSCN(s). A complex oxide layer containing a Cu(I) inner and a Cu(II) outer layer is formed under the CuSCN layer leading to metal passivation. At this stage of the process soluble Cu(I) and Cu(II) species are detected. Region II corresponds to the onset of Cu passivity through the formation of a complex film. The passive region extends up to a certain critical value (breakdown potential) associated with the localized corrosion of base Cu (region III). The breakdown potential decreases linearly as the KSCN concentration increases. The localized corrosion process is apparently related to the nucleation and growth of an unstable Cu(SCN)2 layer in equilibrium with Cu(SCN)−3(I). A reaction pathway is presented to account for the overall electrochemical behaviour of Cu in borate buffers containing KSCN.